Clinical and epidemiological aspects of patients injured by stingrays in the state of Pará, Brazil (Acta Scientiarum. Health Sciences, 2024)
The objective of this study was to outline the clinical-epidemiological profile of patients injured by stingrays from 2007 to 2021. A descriptive study was carried out through an epidemiological retrospective of ichthyism in 20 municipalities in Pará belonging to the Amazon Basin. Notified cases were obtained from the Notifiable Diseases Information System, where the following variables were investigated: socioeconomic profile, affected anatomical region, local and systemic clinical symptomatology. Treatment evolution regarding death and cure was also evaluated. Data were statistically evaluated using the chi-square test, at 5% significance level. A total of 737 cases of accidents caused by stingrays were reported during the period. Of these, 438 forms were not completed with the education data of the patients treated, followed by 158 forms not completed for the race item. Accidents caused by stingrays tend to happen to brown men, aged over 20 years, with incomplete secondary education, living in urban areas, with accidents occurring mainly on the region's beaches. The foot and leg were the most affected regions (p